A regularized boundary element formulation with weighted-collocation and higher-order projection for 3D time-domain elastodynamics. (August 2018) - Pak, Ronald Y.S.; Bai, Xiaoyong
Abstract: To advance Time-Domain Boundary Element Methods (TD-BEMs), a generalized direct time-integration solution method for three-dimensional elastodynamics is presented in this paper. On the basis of a general decomposition of time-dependent point-load Green's functions into a singular and regular part, a regularized boundary integral equation for the time domain is formulated and implemented via a variable-weight multi-step collocation scheme that allows for different orders of time projection for the boundary displacements and tractions. The benefits and possibilities of improved performance by suitable collocation weights and the solution projection choices are illustrated via two benchmark finite-domain and infinite-domain problems.